A randomized controlled trial of a mindfulness-based intervention program for people with schizophrenia: 6-month follow-up - Wang, Li-Qun (Neuropsychiatr Dis Treat, 2016)
Mindfulness-based interventions have been increasingly evidenced to be effective in different mental illnesses but limited in schizophrenia. This single-blind, multisite randomized controlled trial tested the effects of a mindfulness-based psychoeducation group program (MPGP in addition to usual care) versus a conventional psychoeducation group program (CPGP) versus treatment-as-usual (TAU) alone, in schizophrenia spectrum disorders over a 6-month follow-up. In each of the two study sites (outpatient clinics), 69 outpatients with schizophrenia or its subtypes (N=138) were randomly allocated to one of the three study groups (n=46) after baseline measurements and underwent 6 months of intervention. Primary outcomes including patients’ mental state and rehospitalization rate and other secondary outcomes were assessed at entry and at 1 week and 6 months. One hundred and thirty-one (95%) participants completed the interventions assigned and one to two post-tests. Multivariate analyses of variance (followed by univariate contrast tests) indicated that the MPGP participants reported greater reductions in their psychotic symptoms (P=0.003) and length/duration of rehospitalizations (P=0.005) at 6-month follow-up. Patients in the MPGP group also reported greater improvements in their insight into illness/treatment (P=0.0008) and level of functioning (P=0.002) than the CPGP and TAU alone at the 1-week and 6-month follow-up. Overall, the findings suggest that MPGP can be useful in improving the short- to medium-term clinical outcomes of outpatients with schizophrenia spectrum disorders, not only in terms of their mental state and risk of relapse but also their insight into illness/treatment and psychosocial functioning.